Enhancing the participation of small-scale fishing sector in decision-making: Good practices from Atlantic in EU. (July 2021) - Murillas-Maza, Arantza; García-Allut, Antonio; Aranda, Martin; Pazos, César; Iriondo, Ane; Montero, Miriam
Abstract: The aim of this research is to provide a comprehensive analysis of the degree of participation and influence of Small-Scale Fisheries (SSF) across the European Union Atlantic Area putting forward a set of good practices and recommendations for policymakers, Non-Governmental Organisations and SSF representatives. The actual margin for enhancing the degree of influence of SSF on decision-making processes is still large. Moving towards community-based management models from the current hierarchical models is compulsory. A set of measures have been adopted in Western Waters following participatory processes, introducing self-management and co-management tools at the local and regional levels. This research goes beyond the governance model addressing issues such as the increase of influence when the final decision-makers promote a certain devolution of power to the local/regional levels carried out in parallel with reinforcing the capacity of the SSF representatives to exercise such power. Highlights: The margin for enhancing the influence of SSF on decision-making is still large. Scarce examples of SSF co-management models available at Western Waters. High number of organisations representing SSF but low connectivity at Western Waters. MS to include an SSF Action Plan, EMFF operational programme, including governance. To enhance the definition of the decision-making rules, guidelines, and timing.